Beliefs About Wealth and Mobility are Related to Evaluations of Economic Inequalities - Samuelson, Arvid; Burkholder, Amanda R.; Dahl, Audun; Sriram, Ameya; Killen, Melanie (Social justice research, 2025)
Poverty lowers physical and psychological wellbeing. Yet, as economic inequality has grown in the United States, a minority of Americans list it among their top concerns. To understand the psychological underpinnings of this paradox, this study surveyed U.S. young adults ( N = 184, M age = 19.43) about their beliefs around social mobility, attributions of individual sources to wealth, and perceptions of U.S. wealth and wage inequalities. We were particularly interested in the difference between what participants believed were the actual levels of economic inequality and what their ideal levels were–their perceived-ideal disparity. Results revealed that the association between attributions of wealth to individual sources and their perceived-ideal disparity was mediated by perceptions of societal mobility. These findings help to explain attitudes that contribute to perpetuating wealth inequalities.